Viral‐specific T‐cell response in hemorrhagic cystitis after haploidentical donor stem cell transplantation. Issue 6 (25th October 2017) - Apiwattanakul, Nopporn; Hongeng, Suradej; Anurathapan, Usanarat; Pakakasama, Samart; Srisala, Supanart; Techasaensiri, Chonnamet; Andersson, Borje S.
Abstract: Viral hemorrhagic cystitis (HC) after hematopoietic stem cell transplantation (HSCT) can be devastating. Standard treatment modalities have not been well established, but immune reconstitution may be necessary for sustained viral clearance. We studied five pediatric patients who developed viral HC after haplo‐identical HSCT. All patients developed virus‐specific CD4‐ and CD8‐positive T cells, and the emergence of these viral‐specific T cells was temporally associated with successful viral clearance.